Killer app - Carey, S. (Melbourne : Penguin Group (Australia), 2013)
When Roma's friend Michael downloads a mysterious app, all of her friends are curious. Inside the Dead Boring game, they all see different things. Michael says the only way to play it is if they all play at the same time, at 10.00pm. For the rest of them, the game is wondeful, and they can do what they love. But for Roma, it's a nightmare. Soon it all goes dreadfully wrong, and they can't get out. What is this game, and more importantly, who's behind it?.
Imprint: e-penguin.
For primary school age.
Keywords: Computer games -- Juvenile fiction; Horror tales; Video games -- Juvenile fiction; Horror & ghost stories, chillers (Children's / Teenage); Australian